Nonlinear Superchiral Meta‐Surfaces: Tuning Chirality and Disentangling Non‐Reciprocity at the Nanoscale. (17th April 2014) - Valev, V. K.; Baumberg, J. J.; De Clercq, B.; Braz, N.; Zheng, X.; Osley, E. J.; Vandendriessche, S.; Hojeij, M.; Blejean, C.; Mertens, J.; Biris, C. G.; Volskiy, V.; et al.
<x xml:space="preserve">Abstract</x> Circularly polarized light is incident on a nanostructured chiral meta‐surface. In the nanostructured unit cells whose chirality matches that of light, superchiral light is forming and strong optical second harmonic generation can be observed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>